Popis gnezditvene naselbine brinovke Turdus pilaris v Ključih pri Rodinah - Kozinc, Boris (Acrocephalus, 1998)
The breeding colony of Fieldfares discovered on April 25th 1998 at Ključi comprised 18 nests. The breeding success was poor, for only 11 young left three nests (or o.61 young per nest). All the nests were situated in lime trees. Tilia platyphyllos and Tilia cordata at an average height of 9.5 metresfrom the ground. Half of the nests were hidden in mistletoe.
Keywords: ornitologija; ptice; bird; opazovanje; brinovka; Rodine